La réduction du temps de travail : quels enjeux pour la santé des salariés âgés ? - Serge Volkoff (Perspectives Interdisciplinaires sur le Travail et la Santé)
The reduction of the legal working week in France has come at a time when the active population as a whole is ageing. While the reduction, of itself, provides an opportunity for cutting back the workload, it often involves other modifications to the organization of work, such as an increase in shiftwork and night work, greater time pressure, and fewer possibilities for preparing and anticipating changes in the job situation. The available knowledge of work and ageing in the fields of ergonomics and work psychology allow us to question the consequences of these modifications for elderly workers.